Elevated Serum Tumor Markers (HE4 and ROMA Score) and Increased Treg Cells Distinguished Ovarian Cancer and Benign Tumor - Hutapea, Manuel; Syamsudin, Syamsudin; Kurnia, Iin; Fattah, Miswar; Hikmat, Ujang Saeful; Putri, Vinessa Gracia (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Tumor markers such as human epididymis protein 4 (HE4), cancer antigen 125 (CA-125), and risk of ovarian malignancy algorithm (ROMA) are frequently utilized for diagnostic and prognostic purposes. Lymphocytes, essential immune cells, play a significant role in eliminating cancer cells. However, the precise correlation between tumor markers and lymphocytes remains incompletely elucidated. The aim of this study was to explore the correlation between tumor markers and lymphocyte subtype profiles in differentiating ovarian cancer and benign tumors.METHODS: This was a cross-sectional study involving 12 ovarian cancer and 17 benign ovarian tumor patients. Blood samples were collected for the characterization of T lymphocytes, B lymphocytes, natural killer (NK), and T regulatory (Treg), which were analyzed using flowcytometry. Additionally, tumor markers HE4 and CA-125 were measured from patient serum using the chemiluminescent microparticle immunoassay (CMIA) method.RESULTS: Benign ovarian tumors and ovarian cancer can be distinguished by a significant increase in HE4 levels (p=0.004), ROMA (p=0.004), and Treg cells (CD4+/CD25+/FOXP3+, p=0.017). Furthermore, the correlation between tumor markers and lymphocytes indicates that an increase in ROMA was weakly correlated with an increase in the percentage of T regulatory cells (CD4+/CD25+/FOXP3+, r=0.553, p=0.006) and B lymphocytes (CD19+, r=0.528, p=0.010), accompanied by a decrease in the number of T lymphocytes (CD3+, r=-0.598, p=0.003), T helper lymphocytes (CD3+CD4+, r=-0.594, p=0.003), and cytotoxic lymphocytes (CD3+CD8+, r=-0.510, p=0.013).CONCLUSION: The elevation of serum tumor markers (HE4 and ROMA) accompanied by an increase in Treg cells can distinguish between benign ovarian tumor patients and ovarian cancer patients.KEYWORDS: tumor marker, CA-125, HE4, ROMA, subtype of lymphocytes, ovarian cancer